Altered Brain Functional Connectivity at Resting-State in Patients With Non-arteritic Anterior Ischemic Optic Neuropathy - Zhao, Pengbo; Lv, Han; Guo, Pengde; Su, Yan; Liu, Ming; Wang, Yan; Hua, Haiqin; Kang, Shaohong (Frontiers in Neuroscience, 2021)
Purpose: To investigate the possible changes in functional connectivity (FC) in patients with non-arteritic anterior ischemic optic neuropathy (NAION) using resting-state functional MRI (fMRI). Methods: Thirty-one NAION patients and 31 healthy controls were recruited and underwent resting-state fMRI scans. Regions of interest (ROIs) were defined as bilateral Brodmann’s area 17 (BA17). FC analysis was performed between the ROIs and the rest of the brain regions, and the between group comparisons of FC were performed. We conducted correlation analysis between the FC changes and the clinical variables in NAION patients. Results: Compared with healthy controls, patients with NAION showed significantly decreased FC between the left BA17 and the right inferior frontal gyrus, left caudate nucleus. As for the right BA17, patients exhibited significantly increased FC with the left olfactory gyrus and decreased FC with the right superior frontal gyrus (SFG), right insula. Moreover, FC values between the right insula and the right BA17 were positively correlated with the right side of mean sensitivity in the central visual field (r = 0.52, P < 0.01) and negatively correlated with the right side of mean defect in the central visual field (r = −0.55, P < 0.01). Conclusion: Our study indicated that patients with NAION showed significantly abnormal functional reorganization between the primary visual cortex and several other brain regions not directly related to visual function, which supports that NAION may not only be an ophthalmic disease but also a neuro-ophthalmological disease.